2006
DOI: 10.1007/s10522-006-6495-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Anti-ageing Effects of Curcumin in Aged Rat Brain Regions

Abstract: This study investigated the influence of chronically administered curcumin on normal ageing-related parameters: lipid peroxidation, lipofuscin concentration and intraneuronal lipofuscin accumulation, activities of the enzymes superoxide dismutase (SOD), glutathione peroxidase (GPx), and Na(+), K(+), -adenosine triphosphatase (Na(+), K(+), -ATPase) in different brain regions (cerebral cortex, hippocampus, cerebellum and medulla) of 6- and 24-month-old rats. In normal ageing, lipid peroxidation and lipofuscin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 38 publications
4
80
1
Order By: Relevance
“…The neuroprotective effect of curcumin is exerted via various intra-and extra-cellular mechanisms in the central nervous system, which are responsible for its antioxidant and anti-inflammatory properties (Bala et al, 2006;Mythri & Bharath, 2012). Curcumin could reduce N-methyl-D-aspartate (NMDA)-mediated excitotoxic cell damage through modulation of NMDA receptor activity and attenuating NMDA receptor-mediated calcium rise, leading to a lower rate of apoptosis and enhancing cell viability (Matteucci et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of curcumin is exerted via various intra-and extra-cellular mechanisms in the central nervous system, which are responsible for its antioxidant and anti-inflammatory properties (Bala et al, 2006;Mythri & Bharath, 2012). Curcumin could reduce N-methyl-D-aspartate (NMDA)-mediated excitotoxic cell damage through modulation of NMDA receptor activity and attenuating NMDA receptor-mediated calcium rise, leading to a lower rate of apoptosis and enhancing cell viability (Matteucci et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…CUR represents the pungent principle of curry and is used as a food color in various countries [2]. It exhibits an extremely broad spectrum of biological activities [3,4], which comprise anti-inflammatory [5], antioxidant [6], chemosensitizing [7], radiosensitizing [8], antiangiogenic [9], neuroprotective [10], antimicrobial [11], antiviral [12], antifungal [13], and wound-healing [14] properties, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Tumeric contains curcumin, demethoxycurcumin and bisdemethoxycurcumin which is potential as antioxidant and neuroprotective agent. [14][15][16] Its highly lipophylic character would increase curcumin disposition in the brain. 17 In vitro and in vivo studies showed that curcumin could prevent neurodegenerative process caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%